The hedge fund game - Foster, D; Young, H (2008)
This paper examines theoretical properties of incentive contracts in the hedge fund industry. We show that it is very difficult to structure incentive payments that distinguish between unskilled managers, who cannot generate excess market returns, and skilled managers who can deliver such returns. Under any incentive scheme that does not levy penalties for underperformance, managers with no investment skill can game the system so as to earn (in expectation) the same amount per dollar of funds under management as the most skilled managers. We consider various ways of eliminating this “piggyback effect,” such as forcing the manager to hold an equity stake or levying penalties for underperformance. The nature of the derivatives market means that none of these remedies can correct the problem entirely.